Ipsilateral and contralateral carotid stenosis contribute to the outcome of reperfusion treatment for ischemic stroke - Viticchi, Giovanna; Falsetti, Lorenzo; Riva, Alice; Paolucci, Silvia; Malatini, Simone; Guerrieri, Emanuele; Bartolini, Marco; Silvestrini, Mauro (Frontiers in Neurology, 2023)
Ipsilateral and contralateral carotid stenosis (ICS, CCS) influence acute ischemic stroke (AIS) severity and prognosis. Few data are available about their impact on reperfusion therapies efficacy. Aim of this study was to evaluate the impact of ICS and CCS on the effect of intravenous thrombolysis (IT), mechanical thrombectomy (MT) or both and of antiplatelet therapy (AT). We enrolled all the consecutive patients admitted for AIS to our Stroke Unit and submitted to IT, MT, IT+MT or AT. We established the presence of a significant ICS or CCS (≥ 70%) by ultrasound examination or brain angio-CT or MRI. Clinical and instrumental information were collected; delta National Institutes of Health Stroke Scale (NIHSS) from pre-treatment to patients' discharge was employed as the main outcome measure. 460 subjects were enrolled, 86 with ICS and 38 with CCS. We observed a significant linear trend of deltaNIHSS between carotid stenosis categories for patients undergoing IT (p=0,011), MT (p=0,046) and MT+IT (p=0,040), but no significant trend among subjects receiving no reperfusion treatments was observed (p= 0,174). According to our findings, ICS and CCS negatively influence AIS patients 'outcome treated by interventional therapies. ICS might exert an unfavorable effect both by cerebral hypoperfusion and by continuous microembolization toward ischemic area, while CCS is probable involved in reducing the collateral circles effectiveness. The importance of early carotid stenosis detection and treatment should then be reevaluated not only to manage the prevention approaches but also to obtain insights about post-stroke treatment strategies efficacy.